Two Versus Three Narrow-Diameter Implants with Locator Attachments Supporting Mandibular Overdentures: A Two-Year Prospective Study - Ali M. El-Sheikh; Omar F. Shihabuddin; Sahar M. F. Ghoraba (International Journal of Dentistry)
Purpose. To compare treatment outcome (survival rate, condition of hard and soft peri-implant tissues) and prosthodontic maintenance requirements of two versus three narrow-diameter bone level implants with Locator attachments supporting mandibular overdentures. Materials and Methods. Twenty completely edentulous patients with atrophic mandibles were treated. Ten patients (Group A) were treated with overdentures supported by two narrow (3.3-mm diameter) implants (Straumann AG, Basel, Switzerland) and ten patients (Group B) were treated with overdentures supported by three narrow implants. Locator (Zest Anchors, USA) attachments were used for prosthetic anchorage. Standardized clinical and radiographic parameters (survival rate, plaque index, calculus index, gingival index, bleeding index, probing depth and marginal bone loss) were evaluated at the time of the completion of the prosthetic treatment (baseline) and after 6, 12 and 24 months of functional loading. Prosthodontic maintenance requirements were also scored. Results. Only one implant was lost (Group B) during the healing period. There were no significant differences with regards to any of the studied clinical and radiographic parameters between the two groups (𝑃>0.05). Few prosthetic complications were recorded. Conclusions. No need to insert more than two narrow-diameter bone level implants with Locator attachments in cases of atrophic mandible to support an overdenture, however, long-term prospective studies are required to support this notion.